Writers' & artists' yearbook 2017 : the essential guide to the media and publishing industries : the perfect companion for writers of fiction and non-fiction, poets, playwrights, journalists, and commercial artists.: the essential guide to the media and publishing industries : the perfect companion for writers of fiction and non-fiction, poets, playwrights, journalists, and commercial artists. ([2016]) - Unknown
No abstract available